Analysis of Internal Stress Distribution and Mechanics Characteristics of Pre-existing Cavity in Brittle Rock Under Triaxial Cyclic Loading - Zhou, Xiang; Li, Jiangteng; Lin, Hang (Frontiers in Earth Science, 2020)
Abstract: In order to reveal the internal stress distribution and failure characteristics of pre-existing cylindrical cavity in granite under triaxial cyclic loading, bonded particle models containing cavity were established to investigate the variation of crack propagation, stress distribution, micro-cracks number, elastic modulus and poisson's ratio with the increase of cavity diameter. The results show that the cavity diameter has a significant effect on the tensile crack, compression-shear failure zone and compressive stress distribution. The peak strength decreases as the diameter of the cavity increases. However, the number of cracks increases and the plastic deformation increases more obviously. With the increase of the cyclic axial stress, the decreasing rate of the elastic modulus shows the rule of ‘first slow, fast later’, and the poisson's ratio increases. The distribution of local stress of σ1, σ2 and σ3 well explains the behavior of the cracking surrounding the circular cavity.